Global Economic and Political Ramifications of the Russian-Ukrainian War - Goni, Lawan Malami; Sani, Nabeelah Muhammad (Kashere Journal of Politics and International Relations, 2025)
The ongoing Russian-Ukrainian war, which began in February 2014, has escalated into a full-scale conflict, resulting in a significant humanitarian crisis, tens of thousands of deaths, and a substantial impact on the global economy. This paper uses a documentary data collection method to examine the economic consequences of the war on the world economy. Furthermore, it investigates the effects of the conflict on international politics, highlighting the tensions between Russia and Ukraine. The findings of this study suggest that the war has far-reaching implications for global stability, trade, and economic development. To mitigate these effects, this paper recommends that NATO adopt a more democratic approach to resolving the conflict and those mediation efforts by the United Nations and European Union be employed to end the war and prevent further bloodshed and economic consequences. Ultimately, this study contributes to our understanding of the complex relationships between conflict, economy, and international politics, and provides insights into the need for a multilateral approach to resolving the Russian-Ukrainian war.